A case of aesthetic and functional rehabilitation for loss of posterior support - Nadiyah Abdullah Zawawi; Zethy Hanum Mohamed Kassim; Mohd Khairul Firdaus Mazlan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: In patients with prolonged posterior edentulism, compensatory changes such as overclosure and supraeruption of the remaining teeth frequently occur, leading to disruption of the occlusal plane and posing major challenges in prosthodontic rehabilitation to achieve optimal function, aesthetics, and comfort. Purpose: This case report highlights the stepwise multidisciplinary management and techniques involved in prosthodontic rehabilitation in a case using fixed and removable prostheses, emphasizing the method of restoring vertical dimension to achieve functional occlusion. Case: A 68-year-old retired Malay male presented with complaints of defective crowns, multiple missing teeth, non-carious cervical lesions, and generalized tooth surface loss. Key findings included posterior supraeruption, uneven occlusal planes, and generalized horizontal bone loss. Diagnoses included pulp necrosis with apical periodontitis, biofilm-induced gingivitis on a reduced periodontium, and partial edentulism. Case Management: Treatment began with stabilization of the primary conditions, followed by the extraction of unrestorable teeth. The vertical dimension was then re-established using interim acrylic dentures at centric relation, allowing assessment of the patient’s adaptation. Preliminary restorative treatment included root canal therapy for non-vital teeth and placement of fiber posts. In the final restorative phase, the occlusal plane was corrected using lithium disilicate crowns, and posterior support was restored with cobalt-chromium partial dentures. Functional and aesthetic outcomes were achieved through meticulous planning and execution. Conclusion: This case highlights the successful rehabilitation of a patient with increased occlusal vertical dimension using a multidisciplinary approach. The integration of fixed and removable prostheses, along with patient compliance, ensured functional and aesthetic outcomes, emphasizing the importance of comprehensive treatment planning in prosthodontics.